(untitled) (CR. Conservación y Restauración, 2025)
Costa Rica has a diverse archaeological heritage that requires research, protection, conservation, and dissemination. Fundamental to protection against illicit trafficking has been the provision and implementation of a legal framework prohibiting the illegal possession, trade, and export of archaeological property, for it, Law N° 6703 was adopted in 1982. Its validity for four decades has generated interest in this document to expose experiences of archaeological assets of Costa Rica recovered through seizures and repatriations, a joint work with different government entities and civil society and that involves dissemination activities towards specialized and general public, to raise awareness about the patrimonial wealth inherited by our ancestors and to prevent the illicit trafficking.